Different paths to free trade : the gains from regionalism - Freund, Caroline (2000)
Examines alternative liberalization strategies to determine how they influence trade flows and welfare. Compares free trade reached through expanding regional trading blocs to free trade accomplished by multilateral negotiation. Provides empirical evidence from the European Union that is consistent with the model.